Shaking table tests and seismic design suggestions for innovative suspended ceiling systems with detachable metal panels. (1st April 2021) - Luo, Zheng; Xue, Jianyang; Zhou, Tiegang; Qi, Liangjie; Zhao, Xiangbi
Highlights: An innovative suspended ceiling system was proposed and tested by shaking table. A proposed seismic solution for integrating lightings into ceilings was verified. Comparative tests were conducted on a flat type and a double-level type ceiling. The seismic damage characteristics and damage threshold of HPSC were obtained. Abstract: Recent severe earthquakes revealed that a suspended ceiling system was one of the most fragile non-structural components in buildings, with damage to ceilings causing serious economic losses. Suspended ceilings with detachable panels are widely used because they make the maintenance of facilities above the ceiling convenient, but their poor structural integrity makes them prone to earthquake damage. An innovative type of ceiling system, called a hook-on panel suspended ceiling (HPSC), was proposed to investigate and improve the seismic performance of a suspended ceiling with detachable panels, and full-scale specimens with integrated light fixtures were tested. A total of four shaking table tests were carried out for two types of HPSCs with two boundary conditions. The seismic responses and damage patterns of these HPSCs were compared and analyzed. In addition, the influence of the perimeter constraint on the seismic behavior of the HPSC was investigated. The test results showed that the perimeter constraint of the ceiling effectively reduced seismic response of the flat type of HPSC. After all the loading cases, the frequency and damping ratio of the HPSC did not change significantly, indicating that HPSC was only slightly damaged during the earthquake. The ratio of the panel dropping area to the overall ceiling area was less than 5%, showing that the HPSC had a good seismic performance. Finally, the seismic calculations and countermeasures were provided to facilitate the HPSC as a type of anti-seismic suspended ceiling.